Biodiversity Protection in European Union Agriculture - Kociszewski, Karol (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2013)
Biodiversity conservation is an important element of EU environmental policy and it influences certain instruments of the Common Agricultural Policy (agri-environmental programmes, cross–compliance rules, organic farming support). These play an increasingly important role in this policy. However, in some Member States they are insufficiently directed to nature conservation. Direct payments affect an increase in threats to biological diversity, although this impact was restricted in the course of the CAP reform (implementation of a regional system combined with cross-compliance rules). Moreover, the withdrawal or significant reduction of the instrument would result in even greater losses. Low effectiveness of existing activities contributes to the continuous degradation of biological diversity in European rural areas: the specialized payments for farmers in the Natura 2000 network are implemented to a limited extent, specialised support directed for High Nature Values (HNV) farming has not yet been introduced in practice, execution of cross-compliance rules was insufficient. In years 2014-2020 nature conservation within the CAP will grow in importance and it will implicate improvement of the effectiveness of actions implemented in the Member States.